Cervical Ectopic Pregnancy: A Management Dilemma. - Shafiee MN,; Norliza I,; Lim PS,; Shuhaila A,; Mohd Hashim O, (Department of Surgery, UKM Medical Centre, 2012)
A 28-year-old G3P1+1 at 6 weeks period of amenorrhea with a previous Caesarean section presented with per vaginal bleeding. A cervical ectopic pregnancy was confirmed by a transvaginal scan. An intramuscular methotrexate was given followed by intracervical route due to poor decline of the serum βHCG. However, due to persistent increment of serum βHCG, an additional four doses of intramuscular methotrexate with folinic acid rescue were administered and she responded well to the regime. Unfortunately, following the last dose, she developed an episode of excessive per vaginal bleeding which required suction and curettage of the cervical canal. A Foley‘s catheter balloon was placed intracervically as a tamponade and the bleeding was successfully arrested.